8-Methoxypsoralen has Anti-inflammatory and Antioxidant Roles in Osteoarthritis Through SIRT1/NF-κB Pathway - Li, Jichao; Zhang, Zeng; Qiu, Jinan; Huang, Xiaohan (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is mainly manifested by joint pain, stiffness and mobility disorder, which is the main cause of pain and disability in middle-aged and elderly people. In this study, we aimed to explore the role and mechanism of 8-Methoxypsoralen (8-MOP) in the OA model both in vitro and in vivo. The rat chondrocytes were treated with IL-1β, and the proliferation, apoptosis, inflammatory reactions and oxidative stress responses were determined after treatment with different concentrations of 8-MOP. Real-time quantitative polymerase chain reaction (qRT-PCR) and/or Western blot were implemented to check the AMPK/SIRT1/NF-κB expression in chondrocytes. The NF-κB activity was determined by dual luciferase experiment. The pain threshold of OA rat model dealt with 8-MOP and/or the SIRT1 inhibitor EX527 was measured. Our results revealed that 8-MOP evidently reduced IL-1β-mediated apoptosis and inhibition of proliferation, and mitigated the expression of inflammatory cytokines and oxidative stress factors in chondrocytes. Additionally, 8-MOP promoted phosphorylated level of AMPKα，enhanced SIRT1 expression and inhibited the phosphorylation of NF-κB. After treatment with EX527, 8-MOP-mediated protective effects on chondrocytes were mostly reversed. In vivo, 8-MOP obviously improved the pain threshold in the OA rat model and reduced the injury and apoptosis of chondrocytes in the joints. In addition, 8-MOP relieved inflammatory and oxidative stress responses in the articular cartilage via enhancing SIRT1 and repressing NF-κB activation. After the treatment with EX527, the 8-MOP-mediated protective effects were distinctly weakened. In summary, our study testified that 8-MOP alleviates pain, inflammatory and oxidative stress responses in OA rats through the SIRT1/NF-κB pathway, which is expected to become a new reagent for clinical treatment of OA.